Power Generation Using Speed Breakers - Shehar Bano; Anns Nadeem; Abrar Ahmad; Umer Shuja (Institute of Advanced Engineering and Science, 2015)
In the current scenario demand of power is increasing day by day with increasing population. On the other hand energy crisis is also a main issue of today’s life and all there is a shortage of conventional energy resources due to its large usage. So, we have to sort out this problem with a technique which will not only overcome this energy crisis but also should be eco-friendly. Many conventional resources are creating pollution so that’s why focus is towards eco-friendly solution. This project emphasizes on idea which shows that power could be generated by specially designed speed breakers. A large amount of kinetic energy is being wasted on roads on daily basis in different forms which could be use to generate power and this power can be stored in batteries. This project shows clearly how we can generate power by using rack-pinion method where basically linear motion is converted into rotatory motion and then can be used to generate electricity. Large amount of electricity can be generated using this method and this method is eco-friendly.